2007
DOI: 10.1093/europace/eum042
|View full text |Cite
|
Sign up to set email alerts
|

Acute biventricular pacing after cardiac surgery has no influence on regional and global left ventricular systolic function

Abstract: There were no differences in QRS duration during intrinsic rhythm, RA-BiV pacing, and AAI pacing. However, RA-LV and RA-RV stimulations showed a longer QRS duration (P < 0.01 vs. intrinsic rhythm, RA-BiV pacing, and AAI, respectively). Tissue Doppler velocities of the septal and lateral mitral annulus were comparable in all pacing modes. Neither CI nor PAP or PCW showed significant differences during the various pacing configurations. There was a positive correlation between regional (TDI) and global (CI) para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 42 publications
2
9
0
2
Order By: Relevance
“…A number of small single‐center studies have compared Bi‐V pacing to other pacing modalities in the immediate postoperative period following valve surgery, CABG or a combination of both, with mixed results . Given the conflicting data, a recent randomized controlled study by Spotnitz et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of small single‐center studies have compared Bi‐V pacing to other pacing modalities in the immediate postoperative period following valve surgery, CABG or a combination of both, with mixed results . Given the conflicting data, a recent randomized controlled study by Spotnitz et al .…”
Section: Discussionmentioning
confidence: 99%
“…A number of small single-center studies have compared Bi-V pacing to other pacing modalities in the immediate postoperative period following valve surgery, CABG or a combination of both, with mixed results. [17][18][19][20][21][22][23][24][25] Given the conflicting data, a recent randomized controlled study by Spotnitz et al 26 sought to determine if a 3 phase optimization of Bi-V pacing soon after cardiac surgery improved cardiac index (CI). The study revealed no significant improvement in CI, but patients with AV surgery had a 29% increase in CI from Bi-V pacing compared to the control group (P = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al and others [18,22,23] observed greatest benefits in patients with low EF and wide QRS complex. Whereas others, report no significant hemodynamic improvement with these pacing modes or even no adverse effects with RA-RVP in populations with normal ventricular function [19-21]. …”
Section: Discussionmentioning
confidence: 99%
“…The optimum VVD differed from the nominal value, in 5% CO improvement. Overall, optimized BiVP resulted in a CO increase of 10% versus SR. Schmidt and co-workers [19],pointed out the limitation of not using AVD and VVD optimization with BiVP, after not obtaining any HD improvement in CBPG cases.…”
Section: Discussionmentioning
confidence: 99%
“…This is achieved by attaching temporary pacing wires to the right atrium (RA), right ventricle (RV) and LV before closing the sternum. Previous studies of permanent BiV pacing have reported acute improvements in haemodynamic function [14] but attempts to reproduce these findings acutely after cardiac surgery have produced mixed results [510]. In addition, one postoperative study has reported no improvement in coronary conduit flow with BiV pacing compared with atrial synchronous RV pacing [11].…”
Section: Introductionmentioning
confidence: 99%